The Challenges Urbanization in West Africa - World Bank Group (World Bank, Washington, DC, 2018)
The Sahel is experiencing rapid and disorderly urbanization. The capital cities of Bamako, Conakry, and Niamey dominate the urban landscape in their respective countries. In each of these three countries, the economic importance of the capital city is enormous. For instance, Bamako represents about 34 percent of gross domestic product (GDP), whereas Conakry and Niamey each represent about 27 percent of GDP in their respective countries. Furthermore, as their populations are increasing at a faster rate than anywhere else in the world, the attendant youth bulge could turn into either a demographic dividend, whereby cities take advantage of a temporary boom in the working age population to productively employ young people, or a demographic disaster, accompanied by urban instability if cities do not meet these aspirations.